Hydrogen from hydrogen sulphide in Black Sea - Baykara, S. Z.; Figen, E. H.; Kale, A.; Veziroglu, T. Nejat (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Hydrogen sulphide, an acid gas, is generally considered an environmental pollutant. As an industrial byproduct, it is produced mostly during fuel processing. Hydrogen sulphide occurs naturally in many gas wells and also in gas hydrates and gas-saturated sediments especially at the bottom of the Black Sea where 90% of the sea water is anaerobic. The anoxic conditions exist in the deepest parts of the basin since nearly 7300 years, caused by the density stratification following the significant influx of the Mediterranean water through the Bosphorous nearly 9000 years ago. Here, H2S is believed to be produced by sulphur reducing bacteria at an approximate rate of 10000 tons per day, and it poses a serious threat since it keeps reducing the life in the Black Sea. An oxygen-hydrogen sulphide interface is established at 150-200 m below the surface after which H2S concentration starts increasing regularly until 1000 m, and finally reaches a nearly constant value of 9.5 mg/l around 1500 m depth. Hydrogen sulphide potentially has economic value if both sulphur and hydrogen can be recovered. Several methods are studied for H2S decomposition, including thermal, thermochemical, electrochemical, photochemical and plasmochemical methods. In the present work, H2S potential in the Black Sea is investigated as a source of hydrogen, an evaluation of the developing prominent techniques for hydrogen production from H2S is made, and an engineering assessment is carried out regarding hydrogen production from H2S in the Black Sea using a process design based on the catalytic solar thermolysis approach. Possibility of a modular plant is considered for production at larger scale. (c) 2006 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen; hydrogen sulphide; hydrogen energy; hydrogen production; hydrogen sulphide decomposition; hydrogen from Black Sea; SOLAR WATER THERMOLYSIS; THERMOCHEMICAL DECOMPOSITION; SULFUR; H2S; Chemistry; Electrochemistry; Energy & Fuels